Exhaust emissions from the engine running on multi-component fuel - Sendžikienė, Eglė; Makarevičienė, Violeta; Kalenska, Svitlana (Transport, 2012)
Possible alternative raw materials for producing biodiesel fuel are as follows: Camelina sativa oil, fibre linseed oil and waste animal fat. The aim of this work was to analyse the emissions of the engine running on multi-component fuels containing fossil diesel fuel (D), linseed or Camelina sativa oil fatty acid methyl esters (LSME and CME respectively) and beef tallow (TME) fatty acid methyl esters. The concentration of fatty acid methyl esters (FAME) in the mixtures with fossil diesel fuel varied from 10% to 30%. The mass proportion of LSME (or CME) and TME in the mixtures was 1:4. The lowest NOxconcentration in exhaust gases was observed when the mixtures contained 10% of biofuel. For the mixtures containing CME and LSME, NOx concentrations reached 290 and 295 ppm respectively when the engine rotation speed was 1200 min−1 and 370 and 375 ppm respectively when rotation speed was 2000 min−1. CO concentration was the lowest when fuel contained 30% of the FAME mixture. HC concentration was slightly higher when the mixtures containing LSME were used relative to the mixtures containing CME. The amount of HC did not fluctuate considerably (195÷254 ppm) at rotation speeds between 1200 and 2000 min−1. Lower HC concentration was found in exhaust gas when the fuels containing 10% and 20% of biofuel were used. The lowest concentration of polycyclic aromatic hydrocarbons (PAHs) was found when the mixtures contained 30% of biofuel made of LSME or CME corresponding to 30 µg/m3 and 38 µg/m3 at a rotation speed of 1200 min−1 and 640 µg/m3 and 670 µg/m3 at a rotation speed of 2000 min−1 respectively. The greatest amount of smokiness at a high rotation speed of 2000 min−1 was observed when the mixture contained 30% of multi-component biodiesel fuel. It was found that the fuel containing a mixture of 30% of LSME biofuel and 20% of CME biofuel had a small advantage.First Published Online: 26 Jun 2012